A Review and Critique of Advances in the Mitigation of Harmonics - Abdul-Hameed, T. A.; Akorede, M. F.; Abdulrahman, Y. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
In electrical power distribution systems, harmonics has always been a major concern as it can adversely affects the performance of the connected loads when tolerable or recommended standard limits are exceeded. There have been consistent and considerable efforts to study the sources, generation and control of harmonics over the years. This paper presents an extensive literature review of the major works on harmonics in the last two and a half decades. The merits and demerits, advantages and limitations of such work were critically reviewed. It was discovered that a lot remains to be done in the optimization of filters especially the hybrid types and that the design of a filter that can simultaneously mitigate low and higher order harmonics has not been thoroughly researched. This paper is intended as a guide for researchers that are interested in solving harmonics problems to identify the gray areas to concentrate and improve on.